Early-onset neutropenia and mixed phenotype in ADA2 deficiency: diagnostic and therapeutic challenges - Kaplan Sarıkavak, Sibel; Türkyılmaz Uçar, Özge; Cil, Burcu; Hershfield, Michael S.; Tarrant, Teresa K.; Gökmirza, Pinar; Aydoğmus, Çiğdem (Frontiers in Immunology, 2025)
BackgroundAdenosine deaminase 2 deficiency (DADA-2) is an autoinflammatory syndrome caused by mutations in the ADA2 gene. ADA-2 functions as an enzyme in purine metabolism and is presumed to play roles in immune regulation. The clinical spectrum of DADA2varies widely, from vascular inflammation and immune dysregulation to hematological abnormalities, including pure red cell aplasia and hemophagocytic lymphohistiocytosis (HLH). This study aimed to describe the clinical, demographic, and immunological profiles of seven DADA-2 patients to broaden the understanding of its hematological and immunological manifestations and provide insight for early diagnosis and treatment strategies.MethodsData were collected from patient medical records at the Department of Pediatric Allergy and Clinical Immunology, Basaksehir Cam and Sakura City Hospital. The study included genetic analysis, flow cytometry for lymphocyte subpopulations, and ADA-2 enzyme activity measurement.ResultsSeven patients from five families were included, predominantly male, with an average symptom onset at 15 months. Hematological findings were present in all patients, with neutropenia observed at the initial presentation (100%). HLH developed in two patients, contributing to a higher mortality rate of 42.8%. Bone marrow analysis in affected patients revealed hypocellularity and marked T-cell infiltration, with fibrosis detected in one. Despite no evidence of viral triggers (EBV, CMV, VZV, Parvovirus B19), HLH occurred in two patients, suggesting a primary immune dysregulation. Inflammatory and immunodeficiency-related findings were also observed, suggesting a mixed phenotype as the most common presentation. Genotype-phenotype analysis showed that patients with undetectable ADA2 enzyme activity or loss-of-function mutations had more severe hematological involvement. In contrast, a patient with residual enzyme activity exhibited a mixed phenotype. Three patients underwent successful hematopoietic stem cell transplantation (HSCT), reversing disease manifestations.ConclusionOur findings reinforce that DADA2 can initially present as isolated neutropenia, and frequently exhibits a mixed phenotype encompassing hematologic, immunologic, and inflammatory features. HLH is a severe complication that may arise without infectious triggers. Genetic testing for ADA2 should be incorporated into diagnostic panels for congenital neutropenia to avoid delays in diagnosis. Genotype–phenotype correlations offer some prognostic insights, but residual enzyme activity may not fully predict disease severity, underscoring the need for individualized management.